Strategic Feasibility Analysis for Implementing Solar-Powered Electric Vehicle Charging Infrastructure at Universitas Pendidikan Indonesia Bumi Siliwangi Campus Using SWOT Approach - Edypoerwa, Mugni Labib; Padmadewi, Ayu Laksmi; Trisno, Bambang (International Journal of Educational Management and Innovation, 2025)
The increasing adoption of electric vehicles (EVs) in Indonesia requires the development of sustainable charging infrastructure to support emission reductions and national renewable energy targets.Background. This study addresses the lack of solar-powered EV charging stations in higher education institutions, particularly at Universitas Pendidikan Indonesia (UPI) Bumi Siliwangi Campus.Methods. A descriptive research design combined primary data through questionnaire surveys and secondary data from related literature. The SWOT analysis method was applied to identify internal strengths and weaknesses, as well as external opportunities and threats, to assess the feasibility of the proposed system.Results. The findings indicate that UPI has significant internal strengths, such as solar energy potential, green campus initiatives, supporting infrastructure, and an active academic community. Key weaknesses include high investment costs and system maintenance complexity. Externally, opportunities include government policy support and rising public awareness, while threats involve price fluctuations and policy uncertainties. The SWOT matrix positions the strategy in Quadrant II (aggressive), recommending Strengths-Opportunities (SO) strategies.Conclusion. The study concludes that implementing solar-powered EV charging stations at UPI is strategically feasible and can serve as a national model. It supports clean energy transitions and enhances the university's image as a green campus. Future research should consider techno-economic simulations and long-term monitoring.